Evaluation of Anaerobic Microbial Community and Physicochemical Parameters in Small Scale Biodigesters within Uasin Gishu County - Oseso, F. A.; Rono , S.; Kipsumbai, P. (Africa Environmental Review Journal, 2022)
Anaerobic digestion is a sequential biological activity that accepts the efficient capture of methane for energy production. The dependence on fossil and wood fuels as a primary energy source has led to multitudes of problems such as global warming, environmental degradation and human respiratory health complications. The objective of this research was to characterize, identify and study physicochemical requirement of the digesters in relation to methanogenic bacteria identified from cow dung and improve their efficiency in biogas production. Six study sites were selected within Uasin Gishu County, opande, energy, beta farm, radar, nettos and langas, which varied in both volume and biogas production capacity. The cow dung which had been fed to biodigesters were collected aseptically in sterile jars and bacteria were isolated in Biotechnology laboratory, University of Eldoret under anaerobic conditions in a Gas pak jar at a mesophilic temperature of 35oC for seven days. Pure isolates were obtained using streak plate method and evaluation of physicochemical parameters were done in situ. Identification of isolates was done using cultural, morphological and biochemical characteristics. Laboratory scale set up of anaerobic digester for biogas production was done to evaluate their efficiency in biogas production. Three, 500ml erlernymer flask were half filled with cow dung and inoculated with Methanococcus sp. and Methanosaeta sp. separately and a combination of both isolates. This was done in triplicate with different inoculum ratios at 10:500, 20:500 and 30:500 mls, respectively and a control experiment with cow dung alone and allowed to run for 31 days. Gas generated was collected by volume displacement of water and measured at an interval of 0:10, 11:21 and 21:31 days. The temperature and the pH were regulated and monitored regularly. The study identified 7 different anaerobic bacteria species as Methanococcus, Sulfolobus, Methanosaeta, Methanospirillium, Methanosarcina, Methanomicrobium and Methanothrix species. The most predominant methanogenic bacterial strains, which occurred in at least 5 digesters were Methanococcus sp. and Methanosaeta sp which also produced the highest volume of biogas with maximum production being observed in 21-31 days at a ratio of 30:500. Methanococcus sp. and Methanosaeta sp. synergistic activity yielded the highest gas production of 74.23 mls versus 22.50 mls in control and 64.23 mls versus 50 mls from Methanosaeta and Methanococcus sp. respectively. In conclusion, study on the 6 bio digesters showed that physicochemical parameters plays a paramount role in biogas production and should be maintained at an optimum range. The study shows that predominant methanogens Methanococcus sp. and Methanosarcina sp. when inoculated in the digesters increase the quantity of biogas produced. Research recommends that digesters encompasses diverse group of methanogens which works in syntrophic association in the fermentation process thus should be maintained for increase in biogas production.